Multifaceted Janus Textile Simultaneously Achieving Self-Sustainable Thermal Management, Perception, and Protection - Chai, Jialong; Wang, Guilong; Shao, Runze; Ni, Lin; Zhao, Guoqun; Fan, Jintu (Nano-Micro Letters, 2026)
The integration of personal thermal management, perception, protection, and comfort is essential for the development for next-generation textiles capable of performing in complex environments. Janus-designed textiles represent a promising route to this integration, offering adaptive dual-functionality. However, most current designs are limited to single-purpose applications, restricting their effectiveness in truly multifunctional scenarios. Here, we present a multifaceted Janus (X-Janus) textile that overcomes these limitations by combining innovative microporous polytetrafluoroethylene fibers with multidimensional nano- to microscale fibrils and MXene-coated carbon fabric. The X-Janus textile delivers multiple energy-independent functionalities: a spectral Janus design that enables adaptive thermal management through switchable radiative cooling or warming; an electrical Janus design that provides self-powered sensing and energy harvesting; and a wetting Janus design that ensures wearing comfort with waterproofness. Besides, the textile provides comprehensive protection including chemical resistance, electromagnetic interference shielding (56 dB), ultraviolet protection (UPF > 1,500), and flame retardancy. By integrating these advanced features, the X-Janus textile inspires new strategy for self-sustainable textiles, offering scalable solutions for outdoor safety, industrial wearables, and intelligent clothing where multifunctionality and environmental resilience are critical. Highlights: 1 A shear-induced fibrillation strategy enables the continuous fabrication of microporous polytetrafluoroethylene fibers with nano-micro-fibrils with great porosity and strength. 2 A multifaceted Janus design integrates spectral, electrical, and wetting dualities in one textile, realizing adaptive cooling/heating, self-powered sensing, and waterproof breathability without external energy. 3 Comprehensive protection including electromagnetic interference shielding, UV resistance, flame retardancy, and chemical stability for self-sustainable, multifunctional, and comfortable wearables.